Nkrumaism and African Nationalism Ghana's Pan-African Foreign Policy in the Age of Decolonization - Grilli, Matteo (African Histories and Modernities, 2018)
This book examines Ghana's Pan-African foreign policy during Nkrumah's rule, investigating how Ghanaians sought to influence the ideologies of African liberation movements through the Bureau of African Affairs, the African Affairs Centre and the Kwame Nkrumah Ideological Institute. In a world of competing ideologies, when African nationalism was taking shape through trial and error, Nkrumah offered Nkrumaism as a truly African answer to colonialism, neo-colonialism and the rapacity of the Cold War powers. Although virtually no liberation movement followed the precepts of Nkrumaism to the letter, many adapted the principles and organizational methods learnt in Ghana to their own struggles. Drawing upon a significant set of primary sources and on oral testimonies from Ghanaian civil servants, politicians and diplomats as well as African freedom fighters, this book offers new angles for understanding the history of the Cold War, national liberation and nation-building in Africa. .